EMPOWERING WOMEN IN LEADERSHIP: BREAKING BARRIERS AND ACHIEVING EQUALITY - Islomova Sevinch Botirjon qizi (Western European Studies, 2023)
Gender equality in leadership remains an urgent global issue, with women underrepresented in key leadership positions. This article addresses the challenges women face in their pursuit of leadership roles, the barriers that hinder their progress, and the strategies and initiatives that empower women to shatter these barriers. By examining the significance of gender diversity in leadership, the article underscores the importance of promoting equality in leadership roles and offers insights into fostering a more inclusive and equitable society.
Keywords: Women in leadership; gender equality